Copper alloy sheet material, method for manufacturing copper alloy sheet material, and contact component
By using specific alloy composition and heat treatment processes in copper alloy sheets, a boundary area diffusion layer between Si compound and parent phase is formed, which solves the problems of the decrease in strength and poor conductivity of copper alloy sheets at high temperatures, and achieves the improvement of strength and optimization of conductivity at high temperatures.
Patent Information
- Application Number
- CN202180059625.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-10-27
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-10-27
AI Technical Summary
When used in high temperature environments, the strength of existing copper alloy sheets decreases, easily breaks due to stress relaxation, and it is difficult to maintain excellent conductivity.
An alloy composition contains 0.5-5.0 mass % Ni and Co, and 0.10-1.50 mass % Si, and a diffusion layer of 0.5 nm to 5.0 nm is formed in the boundary region between the Si compound and the parent phase. A diffusion layer containing Ni, Co, Cu and Si was observed by a three-dimensional atomic probe field ion microscope.
It effectively suppresses the strength drop caused by temperature rise, improves the strength at high temperature, and maintains excellent conductivity. It is suitable for connectors and other components of electrical and electronic equipment used at high temperatures.
Smart Images

Figure CN116157546B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper alloy plate, a method for manufacturing the copper alloy plate and a contact component. Background Art
[0002] Copper alloy sheets are used in parts of electrical and electronic devices such as smartphones, tablet computers, notebook PCs, sports cameras, automobiles, industrial equipment, robots, and the like, for example, contact parts such as connectors.
[0003] As such a copper alloy sheet material, for example, Patent Document 1 discloses the following technology: in a Cu-Fe-P alloy, the interatomic distance between Fe and P measured by a three-dimensional atom probe field ion microscope is shortened, and the aggregate density of Cu, Fe, and P is increased, thereby producing a copper alloy sheet material having excellent strength and heat resistance during heat treatment during manufacturing.
[0004] In addition, Patent Document 2 discloses the following technology: in a Cu-Ni-Sn-P alloy, the interatomic distance between Ni and P measured by a three-dimensional atom probe field ion microscope is shortened, and the aggregate density of Cu, Ni, and P is increased, thereby producing a copper alloy sheet having excellent stress relaxation resistance.
[0005] In addition, Patent Document 3 discloses a technology for producing a copper alloy sheet material having improved electrical conductivity, stress relaxation resistance and formability by controlling the component composition, elastic limit and crystal orientation in a Cu-Ni-Co-Si alloy.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2009-263690
[0009] Patent Document 2: Japanese Patent Application Publication No. 2009-179864
[0010] Patent Document 3: Japanese Patent Application Publication No. 2016-53220 Summary of the invention
[0011] Problems to be solved by the invention
[0012] Here, in recent years, along with the high-speed communication, high-speed power supply, and increase in the number of sensors, the internal circuit current has increased, and the heat generation has also increased. The above-mentioned electrical and electronic equipment, automobiles, industrial equipment, robots, etc. are used continuously for a certain period of time in a heated state, so their components are sometimes used at high temperatures. In particular, spring electrical contact components such as connectors are prone to high temperatures during high-speed communication and high-speed charging. If such components continue to be used in a high-temperature environment, the strength at room temperature (for example, 25°C) compared to when they were new will decrease, and problems such as material breakage due to stress caused by fitting may occur. In order to prevent this problem, it is ideal that the decrease in strength accompanying the temperature increase is suppressed and the strength at high temperatures (for example, 100°C) is high.
[0013] On the other hand, the above-mentioned components are required to have excellent electrical conductivity.
[0014] However, it is difficult to obtain a copper alloy sheet material having high strength at high temperatures and excellent electrical conductivity while suppressing the decrease in strength accompanying temperature rise in the prior art such as Patent Documents 1 to 3. It should be noted that Patent Documents 1 to 3 do not pay any attention to the strength during use at high temperatures.
[0015] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a copper alloy sheet material having high strength at high temperatures and excellent electrical conductivity, a method for producing the copper alloy sheet material, and a contact component using the copper alloy sheet material, while suppressing a decrease in strength accompanying a temperature increase.
[0016] Means for solving problems
[0017] The inventors of the present application have repeatedly conducted intensive studies and, as a result, have obtained the following findings, and have completed the present invention based on these findings:
[0018] The copper alloy sheet material has an alloy composition, wherein the alloy composition contains at least one of Ni and Co in an amount of 0.5 mass % to 5.0 mass % in total and Si in an amount of 0.10 mass % to 1.5 mass %, wherein the mass ratio of the total content of Ni and Co to the content of Si (Ni+Co) / Si is 2.0 to 6.0, and the balance is copper and unavoidable impurities, and the copper alloy sheet material contains a Si compound containing at least one of Ni and Co and Si in a matrix phase, and a diffusion layer containing at least one of Ni and Co and Cu and Si observed by a three-dimensional atom probe field ion microscope is present in a boundary region between the Si compound and the matrix phase, and the average thickness of the diffusion layer is 0.5 nm to 5.0 nm, thereby suppressing a decrease in strength accompanying a temperature increase and increasing strength at high temperatures. , and has excellent electrical conductivity; and such a copper alloy sheet material can be manufactured by the following manufacturing method: a copper alloy raw material having an alloy composition identical to that of the above-mentioned copper alloy sheet material is subjected to sequential melting and casting [step 1], homogenization [step 2], hot rolling [step 3], surface cutting [step 4], first cold rolling [step 5], first aging heat treatment [step 6], solution heat treatment [step 7], second aging heat treatment [step 8], second cold rolling [step 9], and temper annealing
[10] , wherein in the first aging heat treatment [step 6], the temperature is maintained at 500 to 700°C for 1 to 240 minutes, and in the solution heat treatment [step 7], the temperature is increased from room temperature after the first aging heat treatment [step 6], and the temperature is maintained at 750 to 980°C for 0.10 to 10 seconds before cooling.
[0019] That is, the gist of the present invention is as follows.
[0020] (1) A copper alloy plate having the following alloy composition, wherein:
[0021] Contains at least one of Ni and Co in an amount of 0.5 mass % to 5.0 mass % in total,
[0022] and 0.10 mass % to 1.50 mass % of Si,
[0023] Furthermore, the mass ratio of the total content of Ni and Co to the content of Si is (Ni+Co) / Si of 2.00 or more and 6.00 or less,
[0024] The balance is copper and unavoidable impurities.
[0025] The copper alloy sheet contains a Si compound containing at least one of Ni and Co and Si in the matrix phase.
[0026] In the boundary region between the Si compound and the parent phase, there is a diffusion layer including at least one of Ni and Co and Cu and Si as observed by a three-dimensional atom probe field ion microscope,
[0027] The diffusion layer has an average thickness of not less than 0.5 nm and not more than 5.0 nm.
[0028] (2) The copper alloy sheet material according to (1) above, wherein the alloy composition contains only Co among Ni and Co, and the Co content is 0.5 mass % or more and 5.0 mass % or less.
[0029] (3) The copper alloy sheet material according to (1) above, wherein the alloy composition contains only Ni among Ni and Co, and the Ni content is 0.5 mass % or more and 5.0 mass % or less.
[0030] (4) The copper alloy sheet material according to (1) above, wherein the alloy composition contains both Ni and Co, the Ni content is 0.5 mass % to 4.5 mass %, and the Co content is 0.4 mass % to 2.5 mass %.
[0031] (5) The copper alloy sheet material according to any one of (1) to (4) above, wherein the alloy composition further contains at least one element selected from the group consisting of Mg, Sn, Zn, P, Cr, Zr and Fe in an amount of 0.1 mass % to 1.0 mass % in total.
[0032] (6) A method for producing a copper alloy sheet material, which is the method for producing a copper alloy sheet material according to any one of (1) to (5) above, characterized in that:
[0033] A copper alloy raw material having the same alloy composition as the above-mentioned copper alloy sheet material is subjected to melting casting [step 1], homogenization [step 2], hot rolling [step 3], surface cutting [step 4], first cold rolling [step 5], first aging heat treatment [step 6], solution heat treatment [step 7], second aging heat treatment [step 8], second cold rolling [step 9], and temper annealing
[10] in this order, wherein in the above-mentioned first aging heat treatment [step 6], the temperature is maintained at 500 to 700° C. for 1 to 240 minutes,
[0034] In the solution heat treatment [step 7], the temperature is raised from room temperature after the first aging heat treatment [step 6].
[0035] The obtained temperature is maintained at 750 to 980°C for 0.10 to 10 seconds and then cooled.
[0036] (7) A contact member formed using the copper alloy sheet material according to any one of (1) to (5) above.
[0037] Effects of the Invention
[0038] The copper alloy sheet of the present invention has a suppressed decrease in strength accompanying a temperature rise, has high strength at high temperatures, and is excellent in electrical conductivity. Therefore, it is suitable as a copper alloy sheet for contact parts such as connectors in electrical and electronic equipment, automobiles, industrial equipment, and robots that can be used at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] [ Figure 1 ] Figure 1 A diagram showing an observation example using a three-dimensional atom probe field ion microscope. DETAILED DESCRIPTION
[0040] (1) Copper alloy sheet
[0041] Hereinafter, preferred embodiments of the copper alloy sheet material of the present invention will be described in detail.
[0042] The copper alloy sheet material according to the present invention has an alloy composition, wherein the alloy composition contains at least one of Ni and Co in an amount of 0.5 mass % to 5.0 mass % in total and Si in an amount of 0.10 mass % to 1.50 mass %, wherein the mass ratio of the total content of Ni and Co to the content of Si (Ni+Co) / Si is 2.00 to 6.00, and the balance is copper and unavoidable impurities, and the copper alloy sheet material contains a Si compound containing at least one of Ni and Co and Si in a parent phase, and has a diffusion layer containing at least one of Ni and Co and Cu and Si observed by a three-dimensional atom probe field ion microscope in a boundary region between the Si compound and the parent phase, and the average thickness of the diffusion layer is 0.5 nm to 5.0 nm.
[0043] Hereinafter, the alloy composition of the copper alloy sheet material of the present invention, the Si compound contained in the copper alloy sheet material, and the reasons for limiting the diffusion layer will be described.
[0044] <Alloy composition of copper alloy sheet>
[0045] [Ni and Co components]
[0046] The copper alloy sheet material of the present invention contains at least one of Ni and Co in a total amount of 0.5 mass % to 5.0 mass %. When the total amount of Ni and Co is less than 0.5 mass %, the strength decreases, and when it exceeds 5.0 mass %, the electrical conductivity decreases. From the viewpoint of strength, the total amount of Ni and Co is preferably 0.8 mass % or more, and from the viewpoint of electrical conductivity, it is preferably 4.0 mass % or less. The total amount of Ni and Co is more preferably 1.0 mass % to 3.5 mass %.
[0047] When only Co is contained among Ni and Co, the Co content is preferably 0.5 mass % or more and 5.0 mass % or less.
[0048] When only Ni is contained among Ni and Co, the Ni content is preferably 0.5 mass % or more and 5.0 mass % or less.
[0049] When both Ni and Co are contained, it is preferred that the Ni content is 0.5 mass % to 4.5 mass % and the Co content is 0.4 mass % to 2.5 mass %.
[0050] It should be noted that by containing 0.4 mass% or more of Co, the conductivity is improved compared to the case of Ni alone, but if it exceeds 2.0 mass%, the conductivity may decrease instead. Therefore, when Co is contained, the Co content is preferably 0.5 mass% to 2.0 mass%.
[0051] [Si component]
[0052] The copper alloy sheet of the present invention contains Si in an amount of not less than 0.10 mass % and not more than 1.50 mass %. When the Si content is less than 0.10 mass %, the strength decreases. In addition, when the Si content is higher than 1.50 mass %, the electrical conductivity decreases, and coarse crystal precipitates are easily generated in the ingot, which remain in an undissolved state after the solution heat treatment and are also easy to become the starting point of cracks during bending. From the viewpoint of electrical conductivity, the Si content is preferably 1.25 mass % or less, and more preferably 1.10 mass % or less.
[0053] [(Ni+Co) / Si ratio]
[0054] In the copper alloy sheet of the present invention, the mass ratio of the total content of Ni and Co to the content of Si, i.e., the (Ni+Co) / Si ratio, is 2.00 or more and 6.00 or less. When the (Ni+Co) / Si ratio is less than 2.00, Si is present in excess relative to Ni and Co, and the residual amount of Si in the parent phase increases during aging heat treatment, and the electrical conductivity decreases. When the (Ni+Co) / Si ratio is higher than 6.00, the residual amounts of Ni and Co increase, and the electrical conductivity decreases. From the viewpoint of electrical conductivity, it is preferably 3.00 to 5.00, and more preferably 3.30 to 4.70.
[0055] [Optional additional ingredients]
[0056] The copper alloy sheet material of the present invention may further contain 0.1 mass % to 1.0 mass % in total of at least one selected from the group consisting of Mg, Sn, Zn, P, Cr, Zr, and Fe.
[0057] (Mg)
[0058] Mg has the effect of improving the strength at high temperatures, but tends to reduce the electrical conductivity. Therefore, the Mg content is preferably 0.1% by mass or more and 0.3% by mass.
[0059] (Sn)
[0060] Sn has the effect of improving the strength at high temperatures, but tends to reduce the electrical conductivity. Therefore, the content of Sn is preferably 0.1 mass % or more and 0.3 mass % or less.
[0061] (Zn)
[0062] Zn has the effect of improving Sn plating properties and migration characteristics, but tends to reduce electrical conductivity, so the Zn content is preferably 0.1 mass % or more and 0.5 mass % or less.
[0063] (P)
[0064] P has the effect of suppressing the precipitation of Si compounds on the grain boundaries and increasing the strength, but tends to reduce the electrical conductivity, so the P content is preferably 0.1 mass % or more and 0.3 mass % or less.
[0065] (Cr)
[0066] Cr has the effect of suppressing the coarsening of crystal grains during solution heat treatment, but tends to easily form coarse crystal precipitates during casting and easily become starting points of cracks, so the Cr content is preferably 0.1 mass % to 0.3 mass %.
[0067] (Zr)
[0068] Zr has the effect of suppressing the coarsening of crystal grains during solution heat treatment, but tends to easily form coarse crystal precipitates during casting and easily become starting points of cracks, so the Zr content is preferably 0.1 mass % or more and 0.2 mass %.
[0069] (Fe)
[0070] Fe has the effect of suppressing the coarsening of crystal grains during solution heat treatment, but coarse crystal precipitates are easily generated during casting, and are likely to become starting points of cracks. Therefore, the Fe content is preferably 0.1 mass % to 0.2 mass %.
[0071] [Remainder: copper and unavoidable impurities]
[0072] In addition to the above-mentioned essential components and optional added components, the balance is Cu (copper) and inevitable impurities. It should be noted that the "inevitable impurities" referred to here are roughly components that exist in the raw materials, components that are inevitably mixed in the manufacturing process, and components that are originally unnecessary in copper-based products, but are impurities that are allowed because they are trace amounts and do not affect the characteristics of copper-based products. Regarding components that can be cited as inevitable impurities, for example, non-metallic elements such as sulfur (S) and oxygen (O), and metallic elements such as aluminum (Al) and antimony (Sb) can be cited. It should be noted that the upper limit of the content of the above-mentioned components is 0.05% by mass for each of the above-mentioned components and 0.20% by mass for the total amount of the above-mentioned components.
[0073] <Si compounds>
[0074] The copper alloy sheet material of the present invention contains a Si compound in the matrix.
[0075] The Si compound refers to a compound containing Si and at least one of Ni and Co. In addition to Ni, Co and Si, the Si compound may contain other elements contained in the copper alloy plate, for example, Cu, Mg, Sn, Zn, P, Cr, Zr, and Fe.
[0076] The Si compound is a precipitate formed during the manufacture of the copper alloy sheet. For example, the Si compound is precipitated during the first aging heat treatment [step 6], and then is included in the finally manufactured copper alloy sheet after undergoing a solution heat treatment [step 7] and a second aging heat treatment [step 8].
[0077] <Diffusion layer>
[0078] The copper alloy sheet of the present invention has a diffusion layer containing at least one of Ni and Co and Cu and Si observed by a three-dimensional atom probe field ion microscope in the boundary region between the Si compound and the parent phase. In addition, the average thickness of the diffusion layer is 0.5 nm or more and 5.0 nm or less. The diffusion layer is a region where the concentration of Cu is 20 at % or more and 90 at % or less observed by a three-dimensional atom probe field ion microscope on the copper alloy sheet. The details of the three-dimensional atom probe field ion microscope will be described later.
[0079] The inventors of the present application have discovered that by having the above-mentioned alloy composition and making the average thickness of the diffusion layer observed by a three-dimensional atom probe field ion microscope in the boundary region between the Si compound and the parent phase be greater than 0.5 nm and less than 5 nm, a copper alloy sheet material is obtained in which the decrease in strength accompanying the increase in temperature is suppressed, the strength at high temperature is high, and the electrical conductivity is excellent.
[0080] For the use temperature of electrical and electronic equipment, automobiles, industrial equipment, robots, etc., specifically, the change in strength within the range from room temperature (e.g., 25°C) to high temperature (e.g., 100°C), the influence of the phase transformation of the copper alloy is almost negligible, and the change in strength is considered to be affected by the mobility of dislocations as a thermal activation phenomenon. Therefore, in order to suppress the decrease in strength accompanying the temperature rise and improve the strength at high temperature, it is believed that it is effective to hinder the migration of dislocations by increasing the second phase particles such as solid solution elements and precipitates. On the other hand, if the amount of solute elements added is increased simply to increase the amount of solid solution atoms and the second phase, the problem of decreased conductivity will arise. Therefore, the inventors of the present application believe that in order to suppress the decrease in strength accompanying the temperature rise, improve the strength at high temperature, and make the conductivity good, a method without increasing the amount of added elements is required. The inventors of the present application have found that by forming a diffusion layer of a specified thickness at the interface between the Si compound as a precipitate and the parent phase, it is possible to become a copper alloy sheet material with suppressed strength decrease accompanying the temperature rise, high strength at high temperature, and excellent conductivity. Note that, since the copper alloy sheet material has high strength at high temperatures, it also has high strength at room temperature.
[0081] The diffusion layer is a state where Ni atoms and / or Co atoms and Si atoms exist locally in a high concentration in the Cu matrix, and the diffusion layer suppresses the migration of dislocations. It is speculated that this is one of the reasons for forming a copper alloy sheet material with high strength at high temperatures and excellent conductivity while suppressing the decrease in strength accompanying temperature rise.
[0082] The average thickness of the diffusion layer needs to be 0.5 nm or more and 5.0 nm or less. When the thickness of the diffusion layer is less than 0.5 nm, the strength decreases significantly with the temperature rise, and the strength decreases at high temperatures. In addition, when the thickness of the diffusion layer is greater than 5.0 nm, the solid solution amount increases and the conductivity decreases. The thickness of the diffusion layer is preferably 1.0 nm or more and 4.0 nm or less, and more preferably 2.0 nm or more and 3.0 nm or less.
[0083] (3D Atom Probe Field Ion Microscopy)
[0084] The three-dimensional atom probe method (3DAP method) is an analytical method that can perform three-dimensional composition analysis of nano-precipitates and clusters in metals and semiconductors. The principle is as follows.
[0085] A needle-shaped sample with a tip of about 100 nm is made. After it is moved into a 3DAP device (three-dimensional atom probe field ion microscope), a high voltage is applied in a pulsed manner to cause the atoms to evaporate one by one from the tip of the sample. In addition, by irradiating the tip of the needle with a pulsed laser of a specific wavelength, electric field evaporation is assisted, thereby reducing the probability of sample damage, improving mass resolution, and measuring semiconductors and insulators. The flight time and position of the ions after electric field evaporation due to pulse voltage and laser irradiation are detected using a two-dimensional position detector to measure the two-dimensional coordinate position of each ion. By measuring the time from the time of evaporation at the tip of the needle to the time of arrival at the detector, analysis as a time-of-flight mass spectrometer can also be achieved, so the ion species that have arrived can be determined. Repeated laser irradiation can obtain information on the two-dimensional coordinate position of the ions and information on the depth direction of the sample. Therefore, by performing data analysis that takes into account the shape of the tip of the needle, three-dimensional composition information can be obtained.
[0086] As the 3DAP apparatus, for example, EIKOS-X manufactured by CAMECA can be used.
[0087] The thickness of the diffusion layer is observed in the range from the parent phase to the Si compound, and the concentration profile of each component (Cu, Si, Ni, Co, etc.) of the obtained copper alloy sheet is used, that is, the proximate histogram is obtained. In the case where there are irregularities in the boundary area between the Si compound as the second phase and the parent phase, if a one-dimensional concentration profile is made in a manner that crosses the boundary area, the effects of the irregularities are superimposed, and the precise diffusion layer cannot be defined. Therefore, a proximate histogram based on the isoconcentration surface of a specific element is used. The proximate histogram refers to a one-dimensional concentration profile obtained by calculating the concentration in a direction perpendicular to the isoconcentration surface of a specific element as a reference. In the calculation of the proximate histogram, IVAS, a three-dimensional atomic probe software provided by CAMECA, can be used. For example, Figure 1 This is a close histogram based on the isoconcentration surface with a Ni concentration of 5 at%. Figure 1 This is an observation example of a copper alloy sheet with an alloy composition of 2.3 mass % Ni, 0.55 mass % Si, and the remainder Cu, using a three-dimensional atom probe field ion microscope. From this approximate histogram, it can be seen that in the copper alloy sheet of the present invention, Co, Ni, and / or Cu are diffused at the interface between the Si compound and the parent phase.
[0088] In the approximate histogram, Figure 1 As shown, a region where the Cu concentration is 20 at % to 90 at % is a diffusion layer, and the thickness of the diffusion layer is the length of the region where the Cu concentration is 20 at % to 90 at % in the horizontal axis (distance) direction.
[0089] The average thickness of the diffusion layer is an average value of the thickness of the diffusion layer obtained from a close histogram obtained by measuring each sample (test specimen) sampled at five locations at equal intervals in a direction perpendicular to the rolling direction in the copper alloy sheet.
[0090] As described above, the copper alloy sheet of the present invention has a suppressed decrease in strength with temperature rise, high strength at high temperatures, and excellent conductivity. Therefore, components of electrical and electronic equipment, automobiles, industrial equipment, robots, etc. formed using the copper alloy sheet of the present invention have high reliability in terms of strength and conductivity. For example, even when the operating temperature is from room temperature to high temperature, the strength change is small, a certain strength is exerted, and the conductivity is also excellent, so it becomes a highly reliable component. In particular, even spring electrical contact components such as connectors whose terminals are prone to high temperatures during high-speed communication and high-speed charging become highly reliable components by using the copper alloy sheet of the present invention.
[0091] The tensile strength of the copper alloy sheet material at 100° C. is, for example, 500 MPa or more. The tensile strength of the copper alloy sheet material at 100° C. may be 600 MPa or more, or 690 MPa or more.
[0092] In addition, the copper alloy sheet material of the present invention has high strength at high temperature, and therefore also has high strength at room temperature. The tensile strength of the copper alloy sheet material at 25° C. is, for example, 500 MPa or more, and usually 505 MPa or more.
[0093] The copper alloy sheet material of the present invention can suppress the decrease in strength accompanying the increase in temperature. The difference between the strength at room temperature and the strength at high temperature, for example, the difference between the tensile strength at 25°C and the tensile strength at 100°C is 100 MPa or less, and can also be 70 MPa or less, 55 MPa or less, or 35 MPa or less.
[0094] For example, when the tensile strength of the copper alloy sheet at 25°C is 500 MPa or more and less than 600 MPa, the difference between the tensile strength at 25°C and the tensile strength at 100°C is 100 MPa or less, preferably 70 MPa or less, and more preferably 55 MPa or less.
[0095] When the tensile strength of the copper alloy sheet at 25°C is 600 MPa or more and less than 700 MPa, the difference between the tensile strength at 25°C and the tensile strength at 100°C is 100 MPa or less, preferably 70 MPa or less, and more preferably 55 MPa or less.
[0096] When the tensile strength of the copper alloy sheet at 25°C is 700 MPa or more and less than 800 MPa, the difference between the tensile strength at 25°C and the tensile strength at 100°C is 100 MPa or less, preferably 90 MPa or less, more preferably 70 MPa or less, further preferably 55 MPa or less, and particularly preferably 35 MPa.
[0097] When the tensile strength of the copper alloy sheet at 25°C is 800 MPa or more and less than 900 MPa, the difference between the tensile strength at 25°C and the tensile strength at 100°C is 100 MPa or less, preferably 95 MPa or less, and more preferably 55 MPa or less.
[0098] The tensile strength of the copper alloy sheet material in this specification can be measured using a JIS 13B test piece in accordance with JIS Z2241:2011, for example.
[0099] The electrical conductivity of the copper alloy sheet material of the present invention is, for example, 45% IACS or more, and may be 50% IACS or more, or 55% IACS or more.
[0100] The electrical conductivity of the copper alloy sheet material in this specification can be calculated, for example, by measuring the resistivity by a four-terminal method in a thermostatic chamber maintained at 20° C. (±0.5° C.) with a terminal distance of 100 mm.
[0101] It should be noted that the copper alloy sheet of the present invention is also excellent in the basic bending workability required for connectors and the like. On the other hand, in Patent Documents 1 and 2, in order to improve strength and conductivity, there is little solid solution in the parent phase, and the strength depends largely on dislocation strengthening caused by cold working of more than 60%. Therefore, it is speculated that the copper alloy sheets of Patent Documents 1 and 2 sacrifice the basic bending workability required for connectors.
[0102] The diffusion layer may contain other elements contained in the copper alloy plate material in addition to Ni, Co, Cu and Si, for example, Mg, Sn, Zn, P, Cr, Zr and Fe.
[0103] (2) Method for manufacturing copper alloy sheet
[0104] A method for manufacturing a copper alloy sheet material according to one embodiment of the present invention is described in detail. The method is characterized in that a copper alloy raw material having the same alloy composition as the above copper alloy sheet material is subjected to melting casting [step 1], homogenization [step 2], hot rolling [step 3], surface cutting [step 4], first cold rolling [step 5], first aging heat treatment [step 6], solution heat treatment [step 7], second aging heat treatment [step 8], second cold rolling [step 9], and temper annealing
[10] in sequence, wherein in the first aging heat treatment [step 6], the temperature is maintained at 500 to 700°C for 1 to 240 minutes, and in the solution heat treatment [step 7], the temperature is increased from room temperature after the first aging heat treatment [step 6], and the temperature is maintained at 750 to 980°C for 0.10 to 10 seconds and then cooled. Each step is described below.
[0105] <Melt and Cast [Process 1]>
[0106] In the melting and casting step [step 1], the alloy components are melted in a high-frequency melting furnace under the atmosphere, and the melt is cast to produce an ingot of a predetermined shape (for example, 30 mm in thickness, 100 mm in width, and 150 mm in length).
[0107] <Homogenization [Step 2]>
[0108] In the homogenization step [step 2], a homogenization heat treatment is performed by heating at a predetermined temperature (eg, 1000° C.) for about 1 hour in the air or in an inert gas atmosphere.
[0109] <Hot rolling [process 3]>
[0110] The hot rolling step [step 3] is performed immediately after the homogenization heat treatment, and the sheet is cooled immediately after being made into a predetermined sheet thickness (eg, 10 mm).
[0111] <Surface cutting [Process 4]>
[0112] In the surface cutting step [step 4], a predetermined thickness (eg, about 1 mm to 2 mm) is cut from the surface of the hot-rolled sheet to remove the oxide layer.
[0113] <First cold rolling [Step 5]>
[0114] In the first cold rolling step [step 5], cold rolling is performed to, for example, 0.25 mm to 1 mm.
[0115] <First aging heat treatment [step 6]>
[0116] In the first aging heat treatment [step 6], the temperature is maintained at 500 to 700°C for 1 to 240 minutes. After maintaining at 500 to 700°C for 1 to 240 minutes, the temperature is cooled to room temperature.
[0117] Through the first aging heat treatment [process 6], Si compounds containing Si with an average size of 50 nm to 120 nm are precipitated in the parent phase of the first cold-rolled sheet obtained by the first cold rolling [process 5]. If the temperature is lower than 500°C, the average size of the precipitated Si compounds becomes smaller than 50 nm, and the solid solution of Ni, Co, and Si and the homogenization by diffusion are promoted in the solution heat treatment [process 7]. Si compounds with narrow diffusion layers are easily generated in the second aging heat treatment [process 9], and the average thickness of the diffusion layer of the manufactured copper alloy sheet becomes thinner. In addition, if the temperature exceeds 700°C, the average size of the Si compounds is larger than 120 nm, the undissolved Si compounds in the solution heat treatment [process 7] increase, and the aging strength decreases. It is believed that by performing the first aging heat treatment [process 6] and then the solution heat treatment [process 7] under appropriate conditions, even if the Si compound is temporarily dissolved by the solution heat treatment [process 7], a widely diffused precipitation state is formed during the second aging heat treatment [process 9], which can suppress the strength reduction accompanying the temperature rise and reduce the difference between the room temperature strength and the high temperature strength. On the other hand, in the past, for example, in Patent Document 3, attention was not paid to controlling the diffusion layer by the precipitation state before the solution heat treatment. In the pre-annealing before the solution heat treatment, attention was paid to softening the material and a short-time heat treatment was performed. Therefore, it is believed that an appropriate precipitation state cannot be formed, and a precipitation state with a diffusion layer cannot be formed.
[0118] The average size of the Si compound is the average value of the longest straight line and the shortest straight line connecting two outer edges of each Si compound observed from a bright field image obtained by observing a cross section including the rolling parallel direction and the plate thickness direction using a TEM (Transmission Electron Microscope).
[0119] It should be noted that the Si compound precipitated in the parent phase of the first cold-rolled sheet obtained by the first cold rolling [step 5] by the first aging heat treatment [step 6] undergoes a solution heat treatment [step 7] and a second aging heat treatment [step 8], etc., and therefore the average size and the like are often different from the Si compound contained in the finally manufactured copper alloy sheet material.
[0120] <Solution heat treatment [Step 7]>
[0121] In the solution heat treatment [step 7], the temperature is raised from room temperature after the first aging heat treatment [step 6], and after being held at a reaching temperature of 750 to 980°C for 0.10 to 10 seconds, the temperature is cooled.
[0122] By solution heat treatment [process 7], the second phase particles (Si compound) generated until the first aging heat treatment [process 6] are dissolved. If the temperature is lower than 750°C, the solution does not advance, and it is difficult to form a diffusion layer in the second aging heat treatment [process 9], so the average thickness of the diffusion layer becomes thinner. When the temperature is higher than 980°C, the homogenization brought about by diffusion is also difficult to form a diffusion layer, so the average thickness of the diffusion layer becomes thinner. In addition, when the holding time is longer than 10 seconds, the solid solution atoms diffuse and are homogenized, and the diffusion layer formed by precipitation in the second aging heat treatment [process 8] becomes thinner. When it is less than 0.10 seconds, the diffusion layer becomes thicker. The holding time is preferably 1 to 5 seconds, and more preferably 1 to 2 seconds.
[0123] In the solution heat treatment [process 7], the heating rate is preferably 30°C / second or more. When it is lower than 30°C / second, the following situation occurs: precipitates grow during the heating period, and the average thickness of the diffusion layer becomes thinner. From the viewpoint of control of the arrival temperature, the upper limit of the heating rate is preferably 200°C / second or less. In addition, the cooling rate is preferably 50°C / second or more. When it is lower than 50°C / second, the following situation occurs: coarse precipitates are generated due to cooling from a high temperature, and the average thickness of the diffusion layer becomes thinner.
[0124] <Second aging heat treatment [step 8]>
[0125] The second aging heat treatment [step 8] is performed after the solution heat treatment [step 7].
[0126] As the second aging heat treatment [step 8], for example, it is preferable to adopt a condition of maintaining the temperature at 450 to 500°C for about 3 to 5 hours.
[0127] It should be noted that between the solution heat treatment [step 7] and the second aging heat treatment [step 8], additional cold rolling [step 11] may be performed as necessary.
[0128] In the additional cold rolling [process 11], for example, cold rolling with a rolling processing rate of about 80% or less is performed to make the thickness about 0.1 mm to 0.4 mm. The rolling processing rate (%) is a value obtained by (plate thickness before rolling (mm) - plate thickness after rolling (mm)) / plate thickness before rolling (mm) × 100.
[0129] <Second cold rolling [Step 9]>
[0130] In the second cold rolling [step 9], cold rolling is performed to a thickness of, for example, about 0.09 to 0.36 mm.
[0131] <Quenching and annealing
[10] >
[0132] Tempering annealing
[10] is a process for reducing the anisotropy of mechanical properties including elongation, and is performed, for example, in a salt bath at a temperature of about 400°C for about 15 seconds to 1 minute.
[0133] The copper alloy sheet material of the present invention is extremely useful as a material for forming contact parts such as connectors.
[0134] Although the embodiments of the present invention have been described above, the present invention is not limited to the above embodiments, and includes all aspects included in the concept of the present invention and the claims, and various modifications can be made within the scope of the present invention.
[0135] Example
[0136] Next, in order to further clarify the effects of the present invention, examples and comparative examples will be described, but the present invention is not limited to these examples.
[0137] (Examples 1 to 23 and Comparative Examples 1 to 8)
[0138] In the atmosphere, the alloy components shown in Table 1 and Table 2 are melted by a high-frequency melting furnace, and cast with a mold to obtain an ingot with a thickness of 30 mm, a width of 100 mm, and a length of 150 mm (melting casting [process 1]). Then, after homogenization at 1000°C for 1 hour in the atmosphere [process 2], hot rolling [process 3] is performed to make a hot-rolled plate with a thickness of 10 mm and then immediately cooled. Next, in the surface cutting [process 4], after the surface cutting of 1 mm is performed from the surface to remove the oxide film, the thickness is made to 0.4 mm in the first cold rolling [process 5]. Then, in the first aging heat treatment [process 6], after heat treatment in an argon atmosphere at the temperature and time shown in Table 3 and Table 4, it is cooled to room temperature. In any embodiment and comparative example, Si compounds are precipitated in the parent phase of the first cold-rolled plate obtained by the first cold rolling [process 5] by the first aging heat treatment [process 6].
[0139] Next, in the solution heat treatment [process 7], the temperature is raised from room temperature, and the heat treatment is performed at the reaching temperature and holding time shown in Tables 3 and 4, and water cooling is performed immediately. Next, in the additional cold rolling [process 11], the thickness is 0.1 to 0.38 mm. It should be noted that in Example 17, no additional cold rolling [process 11] is performed. Next, in the second aging heat treatment [process 8], heat treatment is performed under an argon atmosphere at the temperature and time shown in Tables 3 and 4. Next, in the second cold rolling [process 9], the thickness is 0.09 to 0.36 mm. Finally, in the tempering annealing [process 10], heat treatment is performed at 400°C in a salt bath for 30 seconds. A copper alloy sheet is produced by the above operations.
[0140] The average size of the Si compound formed by the first aging heat treatment [step 6], the average thickness of the diffusion layer, the tensile strength at 25° C. and 100° C., and the electrical conductivity were determined by the following method. The results are shown in Tables 1 to 4.
[0141] [Average size of Si compounds]
[0142] The average size of the Si compound precipitated and formed by the first aging heat treatment [step 6] was determined by the following method.
[0143] For the copper alloy plate material cooled to room temperature in the first aging heat treatment [step 6], in a cross section including the rolling parallel direction and the plate thickness direction, a quadrilateral region having a rolling parallel direction dimension and a plate thickness dimension of 100 μm was observed by TEM, and for each Si compound observed from the obtained bright field image, the average value of the longest straight line and the shortest straight line connecting two outer edges was taken as the average size of the Si compound.
[0144] [Average thickness of diffusion layer]
[0145] (Sample Preparation)
[0146] FIB (Focused Ion Beam) was used to prepare the needle-shaped sample for observation using a three-dimensional atom probe field ion microscope. Helios G4 of FEI Company was used to prepare the needle-shaped sample using FIB.
[0147] After extracting a small sample of several μm from a copper alloy plate using the lift-out method, the sample is bonded to a support. Next, the annular processing area is irradiated with a Ga ion beam with an acceleration voltage of 30 kV to form a needle shape. When the sample is cut using a 30 kV Ga ion beam, a damage layer of several 10 nm is formed on the irradiated surface. Therefore, the damaged layer is finally removed using a low-acceleration 5 kV Ga ion beam, thereby obtaining a needle-shaped sample of about 200 nm.
[0148] In the copper alloy sheet material, five samples were taken at equal intervals in a direction perpendicular to the rolling direction to obtain five needle-shaped test pieces.
[0149] (Conditions of 3D Atom Probe Field Ion Microscope)
[0150] As a three-dimensional atom probe field ion microscope (3DAP device), EIKOS-X manufactured by CAMECA was used. The sample was cooled to 50 K for measurement. The wavelength of the irradiated laser was 532 nm, and the energy of the laser pulse was 20 nJ. In addition, the voltage applied to the needle was set to 1 to 5 kV.
[0151] In each needle-shaped sample, three Si compounds were selected and each was observed in the range from the parent phase to the Si compound.
[0152] (Calculation of average thickness of diffusion layer)
[0153] The thickness of the diffusion layer was calculated using the proximity histogram. The calculation of the proximity histogram was performed using IVAS, a three-dimensional atom probe software provided by CAMECA.
[0154] For Examples 1 to 3, 10 and Comparative Example 4, which contain only Ni among Ni and Co, a close histogram is prepared with the isoconcentration surface of Ni concentration being 5 at% as the reference. In addition, for Examples 7 to 9 and 13, which contain only Co among Ni and Co, a close histogram is prepared with the isoconcentration surface of Co concentration being 5 at% as the reference. For Examples 4 to 6, 11, 12, 14 to 23 and Comparative Examples 1 to 3, 5 to 11, which contain both Ni and Co, a close histogram is prepared with the isoconcentration surface of Co concentration being 5 at% as the reference.
[0155] In this approximation histogram, the length of the horizontal axis in the region where the Cu concentration is 20 at% or more and 90 at% or less is obtained as the thickness of the diffusion layer. The thickness of the diffusion layer of 15 diffusion layers obtained for 3 Si compounds in 5 needle-shaped samples is averaged to calculate the average value of the thickness of the diffusion layer.
[0156] [Tensile strength]
[0157] The tensile strength of the copper alloy sheet material was measured by performing a tensile test at room temperature (25° C.) and high temperature (100° C.) atmosphere in accordance with JIS Z2241:2011 using a JIS 13B test piece.
[0158] [Electrical conductivity]
[0159] The electrical conductivity of the copper alloy sheet material can be calculated, for example, by measuring the resistivity by a four-terminal method in a thermostatic chamber maintained at 20° C. (±0.5° C.) with the distance between terminals being 100 mm.
[0160] [evaluate]
[0161] The samples were considered acceptable if the tensile strength at 100° C. was 500 MPa or more, the difference between the tensile strength at 25° C. and the tensile strength at 100° C. was 100 MPa or less, and the electrical conductivity was 45% IACS or more.
[0162] [Table 1]
[0163]
[0164] [Table 2]
[0165]
[0166] [Table 3]
[0167]
[0168] [Table 4]
[0169]
[0170] According to the results of Tables 1 to 4, the alloy compositions of the copper alloy sheets of Examples 1 to 23 are all within the scope of the present invention, and the average thickness of the diffusion layer observed by a three-dimensional atom probe field ion microscope in the boundary region between the Si compound and the parent phase is 0.5 nm to 5.0 nm. Therefore, the difference in tensile strength at 25°C and 100°C is as small as less than 100 MPa, the tensile strength at 100°C is as high as more than 500 MPa, and the electrical conductivity is as high as more than 45% IACS.
[0171] On the other hand, for Comparative Example 1 with a low solution heat treatment temperature and Comparative Example 2 with a high solution heat treatment temperature, the average thickness of the diffusion layer is less than 0.5 nm, the difference in tensile strength between 25°C and 100°C is large, and the tensile strength at 100°C is low. For Comparative Example 3 with a long retention time for the solution heat treatment, the average thickness of the diffusion layer is less than 0.5 nm, and the difference in tensile strength between 25°C and 100°C is large. For Comparative Example 4 with a small total amount of Ni and Co, the tensile strength at 100°C is low. The conductivity of Comparative Example 5 with a low (Ni+Co) / Si ratio is low. The conductivity of Comparative Example 6 with a high (Ni+Co) / Si ratio is low. For Comparative Example 7 with a long first aging treatment time and a large average size of Si compounds precipitated in the first aging treatment, the average thickness of the diffusion layer is less than 0.5 nm, the difference in tensile strength between 25°C and 100°C is large, and the tensile strength at 100°C is low. For Comparative Example 8, in which the first aging treatment temperature was low and the average size of Si compounds precipitated in the first aging treatment was small, the average thickness of the diffusion layer became less than 0.5 nm, probably because homogenization progressed during the solution treatment, and the difference in tensile strength between 25°C and 100°C was large. The conductivity of Comparative Example 9, in which the total amount of Ni and Co was large, and Comparative Example 10, in which the amount of Si was large, was low. For Comparative Example 11, in which the retention time of the solution heat treatment was short, the average thickness of the diffusion layer exceeded 5.0 nm, and the conductivity was low.
Claims
1. A copper alloy plate having the following alloy composition, wherein: Contains at least one of Ni and Co in an amount of 0.5 mass % to 5.0 mass % in total, and 0.10 mass % to 1.50 mass % of Si, Furthermore, the mass ratio of the total content of Ni and Co to the content of Si is (Ni+Co) / Si of 2.00 or more and 6.00 or less, The balance is copper and unavoidable impurities. in, The copper alloy sheet contains a Si compound containing at least one of Ni and Co and Si in the parent phase, In the boundary region between the Si compound and the parent phase, there is a diffusion layer including at least one of Ni and Co and Cu and Si observed by a three-dimensional atom probe field ion microscope, The average thickness of the diffusion layer is not less than 0.5 nm and not more than 5.0 nm.
2. The copper alloy sheet material according to claim 1, wherein: The alloy composition contains only Co among Ni and Co. The Co content is 0.5 mass % or more and 5.0 mass % or less.
3. The copper alloy sheet material according to claim 1, wherein: The alloy composition contains only Ni among Ni and Co. The Ni content is 0.5 mass % or more and 5.0 mass % or less.
4. The copper alloy sheet material according to claim 1, wherein: The alloy composition contains both Ni and Co. The Ni content is 0.5 mass % or more and 4.5 mass % or less, The Co content is 0.4 mass % or more and 2.5 mass % or less.
5. The copper alloy sheet material according to any one of claims 1 to 4, wherein The alloy composition further contains at least one selected from the group consisting of Mg, Sn, Zn, P, Cr, Zr, and Fe in an amount of 0.1 mass % to 1.0 mass % in total.
6. A method for producing a copper alloy sheet material, which is the method for producing a copper alloy sheet material according to any one of claims 1 to 5, characterized in that: A copper alloy raw material having the same alloy composition as the copper alloy plate material is subjected to sequential melting casting [step 1], homogenization [step 2], hot rolling [step 3], surface cutting [step 4], first cold rolling [step 5], first aging heat treatment [step 6], solution heat treatment [step 7], second aging heat treatment [step 8], second cold rolling [step 9], and temper annealing [10], In the first aging heat treatment [step 6], the temperature is maintained at 500 to 700° C. for 1 to 240 minutes. In the solution heat treatment [step 7], the temperature is raised from room temperature after the first aging heat treatment [step 6], The obtained temperature is maintained at 750 to 980°C for 0.10 to 10 seconds and then cooled.
7. A contact component formed using the copper alloy sheet material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Copper alloy sheet superior in stress relaxation resistance
JP2009179864A
Copper alloy sheet for electrical / electronic component excellent in heat resistance
JP2009263690A
Copper alloy sheet excellent in conductivity, stress relaxation characteristic and molding processability
JP2016053220A
Copper alloy sheet, method for manufacturing same, electrical / electronic device heat radiation component, and sealed case
CN111406122A
Cu-Co-Si-BASED COPPER ALLOY FOR ELECTRONIC MATERIAL AND METHOD FOR PRODUCING THE SAME
JP2011252188A